MODEL KEGIATAN PENDIDIKAN TASAWUF DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL SANTRI DI PONDOK PESANTREN IJMA’IYAH BABUSSALAM RUNGKANG - Urwatul Wusqo; Syamsul Arifin; Akhmad Syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the researcher's interest in the model of Sufism education activities implemented to develop the emotional intelligence of students at Ijma’iyah Babussalam Rungkang Islamic Boarding School. The study focuses on identifying the forms and implementation of Sufism education activities as well as examining their role in fostering students’ emotional intelligence. Sufism education is considered an essential aspect of Islamic education because it emphasizes not only intellectual development but also spiritual and emotional growth, which are important for shaping students’ character and behavior.This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation. The sources of data consisted of primary and secondary data. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the research findings.The results indicate that the model of Sufism education activities at Ijma’iyah Babussalam Rungkang Islamic Boarding School is implemented through various religious and character-building activities, including the study of classical Sufism texts, collective dhikr, mujahadah, congregational prayers, discipline habituation, and exemplary conduct demonstrated by the boarding school leaders and teachers. These activities serve as a medium for instilling Sufism values such as sincerity, patience, trust in God (tawakkul), humility, discipline, and proper manners. The implementation of these activities contributes significantly to the development of students’ emotional intelligence, as reflected in increased self-awareness, emotional regulation, self-motivation, empathy, and social skills. Furthermore, students demonstrate positive behavioral changes, becoming more disciplined, respectful, patient, responsible, and capable of building harmonious relationships in their daily lives. Keywords: Sufism Education, Emotional Intelligence, Islamic Boarding School Students.